Social media for improving the students’ vocabulary mastery in ESP Maritime English - Ratnaningsih, Dyah; Purwati, Oikurema; Munir, Ahmad (Universitas Muhammadiyah Sidoarjo, 2024)
The ever-expanding globalization era brings with it a host of new developments in people's lives, including methods of learning, especially when it comes to increasing vocabulary in English, the universal language of communication. Economic issues are greatly impacted by globalization; as a result, trade between countries is growing quickly, and shipping is the most suitable means of transportation. Consequently, there is a growing need for proficient sailors who speak English, especially maritime English, in order to demonstrate clear communication and reduce accidents brought on by miscommunications between crew members and ships. For students in maritime schools, learning Maritime English (ME) terminology is a prerequisite to developing proper communication skills. Social media is one of the teaching strategies used with students at the maritime academy. HIGHLIGHTS: The effectiveness of social media in improving the students’ maritime Englishvocabulary in ESP Maritime English. Several social media such as YouTube, Instagram and Facebook related tomaritime always share the useful knowledge and current issues in globalmaritime world. The social media related to the certain studies are suggested to be followed bythe learners to improve their knowledge and skills.